Performance management around the world: solving the standardization vs adaptation dilemma - Herman Aguinis; Jing Burgi-Tian (IIM Ranchi Journal of Management Studies)
Purpose – Globalization and the COVID (post) pandemic continue to pose significant challenges to managing employee performance across geographic locations because there is a need to simultaneously implement procedures that are standardized and yet applicable to different contexts. This study aims to describe five universal principles in performance management that can be adapted to specific contexts to address the performance management standardization vs adaptation dilemma. Design/methodology/approach – Critical literature review of evidence-based recommendations for practice. Findings – This study describe five universal principles in performance management, how they can be adapted to specific contexts around the world and actions that organizations can take to implement them: (1) cultural congruence, (2) strategic congruence, (3) performance evaluation thoroughness, (4) inclusiveness and (5) effective feedback. Originality/value – This study provide valuable and actionable knowledge for organizations facing performance management challenges around the world.